2005
DOI: 10.2105/ajph.2004.047803
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Obesity and Receipt of Screening Mammography, Papanicolaou Tests, and Influenza Vaccination: Results from the Health and Retirement Study (HRS) and the Asset and Health Dynamics Among the Oldest Old (AHEAD) Study

Abstract: Higher BMI was associated with less frequent receipt of preventive services among middle-aged White women and elderly White women and men. The Healthy People 2010 clinical preventive service goals remain elusive, especially for overweight and obese White persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
131
4
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(147 citation statements)
references
References 42 publications
5
131
4
7
Order By: Relevance
“…There is also limited evidence that obesity is associated with cervical cancer mortality (Calle et al, 2003;Lee et al, 2013). In this context, it is of importance to note that obese women, as in the present study, may be screened less frequently for CC than women of normal weight (Bussiere et al, 2014;Fontaine et al, 2001;Maruthur et al, 2009;Ostbye et al, 2005;Wee et al, 2000), even though the evidence is not entirely consistent (Kim et al, 2009;Reidpath et al, 2002). As Maruthur et al (2009) pointed out, there are several potential barriers to CC screening participation for overweight and obese women.…”
Section: Discussionmentioning
confidence: 59%
“…There is also limited evidence that obesity is associated with cervical cancer mortality (Calle et al, 2003;Lee et al, 2013). In this context, it is of importance to note that obese women, as in the present study, may be screened less frequently for CC than women of normal weight (Bussiere et al, 2014;Fontaine et al, 2001;Maruthur et al, 2009;Ostbye et al, 2005;Wee et al, 2000), even though the evidence is not entirely consistent (Kim et al, 2009;Reidpath et al, 2002). As Maruthur et al (2009) pointed out, there are several potential barriers to CC screening participation for overweight and obese women.…”
Section: Discussionmentioning
confidence: 59%
“…Previous research has suggested that body image avoidance, especially for women, is related to lower quality of life (Cash et al, 2005), greater health risk, and decreased involvement in a variety of life events (Feingold & Mazzella, 1998;Ferrante, Ohman-Strickland, Hudson, Hahn, Scott, & Crabtree, 2006;Latner, 2008;Ostbye et al, 2005). Data for the current study was extracted from a largescale, internet-based survey on how size and body image predict avoidance behaviors in mainly overweight and obese, adult agerepresentative U.S. women and men of varying ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Among morbidly obese individuals, 60% reported avoiding healthcare, in part, for fear of being told to lose weight; however, the most frequently cited reason for avoidance was fear of being undressed in front of the physician. Similarly, Ostbye, Taylor, Yancy, and Krause (2005) presented longitudinal evidence that women with a BMI of 40 or above are the least likely to receive preventative care such as pap smears, mammograms, and influenza vaccinations. Additionally, exercise may be avoided by overweight/obese individuals.…”
Section: Size and Avoidancementioning
confidence: 99%
“…Body mass index was positively associated with mean number of visits to diagnostic health services among primary care patients (Bertakis and Azari 2006). In contrast, the Health and Retirement Study (HRS), conducted in 4439 females aged 50-61 years and the Asset and Health Dynamics Among the Oldest Old (AHEAD) Study in 4045 females and 2154 males aged ≥70 years, found that higher body weight was associated with less frequent receipt of preventive services (Ostbye et al 2005). In a similar way, the present study showed that high body weight was associated with some use of preventive services but participants with high body weight used fewer services, compared to those with normal body weight.…”
Section: Discussionmentioning
confidence: 98%